Immunological and epidemiological investigations into avian malaria in the African penguin during rehabilitation and in breeding colonies - Thiart, Hanlie (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2005.